POTENTIAL AND LEVEL UTILIZATION OF SKIPJACK (Katsuwonus pelamis) IN THE BUNGUS OCEAN FISHING PORT WEST SUMATERA PROVINCE - Brown, Arthur; Purba, Rina Ade Citra (Asian Journal of Aquatic Sciences, 2024)
The skipjack (Katsuwonus pelamis) in Bungus Ocean Fishing Port has been evaluated for its sustainable potential using the surplus production approach method. The findings indicate a strong alignment with the Fox approach model. The estimated sustainable potential for skipjack is 471 tonnes per year, with an ideal effort of 45 trips annually. The analysis indicates a moderate utilization status, with an average skipjack utilization rate of 62.76%. It is evident that around 37.24% of its maximum sustainable potential, equivalent to 154.74 tonnes per year, is still unexplored. In addition, the catch rate of skipjack is relatively high at 96.14%, indicating that there is still some untapped potential, with 3.86% of the optimal fishing effort or two trips per year remaining unused. As a result, it is recommended that a total allowable catch of 341 tons be set in order to ensure the long-term sustainability of skipjack harvesting in the area.